2021
DOI: 10.1111/famp.12695
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Open Dialogue approaches: A scoping review

Abstract: Open Dialogue approaches fall broadly into the area of systemic psychotherapeutic practices. They encourage active participation of families and social networks, and emphasize genuine collaboration within highly integrated systems of health‐care service delivery. These approaches are currently being implemented in a growing number of services across the globe, and in this review, we summarize and discuss insights from papers concerned with the implementation of Open Dialogue. We used a scoping review method, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 39 publications
0
31
0
1
Order By: Relevance
“…This Research Topic pays attention to the fact that Open Dialogue services have been investigated through a range of research methodologies (Freeman et al, 2019 ; Buus et al, 2021 ), including multi-site observational studies used to test feasibility and efficacy (Harding et al, 1987 ; Seikkula et al, 2006 ). Open Dialogue experiences and outcomes have been studied through various survey instruments, including service-user (and family/social network member) self-report scales (e.g., quality of life, or perceived satisfaction with network sessions/service in general).…”
Section: Why This Research Topic?mentioning
confidence: 99%
See 1 more Smart Citation
“…This Research Topic pays attention to the fact that Open Dialogue services have been investigated through a range of research methodologies (Freeman et al, 2019 ; Buus et al, 2021 ), including multi-site observational studies used to test feasibility and efficacy (Harding et al, 1987 ; Seikkula et al, 2006 ). Open Dialogue experiences and outcomes have been studied through various survey instruments, including service-user (and family/social network member) self-report scales (e.g., quality of life, or perceived satisfaction with network sessions/service in general).…”
Section: Why This Research Topic?mentioning
confidence: 99%
“…This challenges conventional ideas on the source of clinical knowledge and definitions of expertise, changing established professional self-understandings and claims (von Peter et al, 2021 ). There are implications for clinical governance including responses to risk, clinical note-taking, discharge, flexible working and the boundaries around clinical work, as well as for training and supervision (Buus et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For several decades, Open Dialogue approaches have been implemented in health care and social care sites across the world (Buus et al, 2017 , 2021 ). Scandinavian implementation studies indicate that adoption of Open Dialogue – like any other organizational change – can generate organizational, professional, and personal resistance which may compromise the core Open Dialogue principles and methods offered at a given site (Brottveit, 2013 ; Søndergaard, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…An Australian study of implementation of Open Dialogue in a private healthcare setting observed tension at the boundaries of organizational systems, challenges between core clinical values, and conflicting expectations of professional practice and performance (Dawson et al, 2019 ). A recent ‘scoping review’ (Arksey & O’Malley, 2005 ) of Open Dialogue implementation studies (Buus et al, 2021 ) found that published studies did not include rich descriptions of the organizational implementation contexts (for instance culture, resourcing and management/leadership factors) or the organizational strategies for the implementation, which made it difficult to draw conclusions regarding what types of implementation would be more effective than others, and under what circumstances. Further, the review highlighted the implementation challenges linked to the flexible and needs-adapted character of the approach that gives it a spirit of indeterminacy (Buus et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation